SAKIP-BASED PUBLIC ACCOUNTABILITY FOR LOCAL GOVERNMENTS IN CENTRAL JAVA PROVINCE - Adinda Nur Afifah; Novi Dirgantari; Bima Cinintya Pratama; Hardiyanto Wibowo (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to examine the effect of the findings of the internal control system, the findings of audit results and total spending on sakip-based public accountability. Free variables used in the study of internal control system findings, audit findings and total spending. As for the bound variable is the sakip quality consisting of the sakip score . This study uses secondary data, namely regional financial reports published by the Financial Audit Agency of the Republic of Indonesia (BPK RI) for the 2018-2020 Fiscal Year and SAKIP Score Data processed from the Ministry ofPan and RB-RI. The selection of samples in this study used a saturated sampling method. The data analysis technique in this study uses descriptive statistics, classical assumptions and multiple liniear regression. The results of this study show that the findings of spi, total spending have no effect on public accountability. And the findings of the audit results have a positive effect on public accountability. Keywords: Internal Control System, Audit Findings, Total Expenditure, SAKIP Quality